Pain-Killer: A 19th Century Global Patent Medicine and the Beginnings of Modern Brand Marketing. (September 2019) - Petty, Ross D.
This paper examines the marketing of a so-called "patent medicine, Perry Davis' Vegetable Pain-Killer, to suggest that many of its 19th century brand marketing practices were precursors to modern brand marketing tactics. Pain-Killer developed a distinctive brand identity through the creation and protection of several brand elements including the product itself, its name, packaging and advertising. The Pain-Killer brand also offered useful content marketing in terms of almanacs, "advertainment" consisting of a book of rhymes and pictures relating to Pain-Killer and a brand story centered in part on its inventor and founder Perry Davis. The Pain-Killer brand enjoyed decades of success reportedly selling 100 million bottles in 60 years (Bismarck Daily Tribune 1905). Ultimately, this brand disappeared because Pain-Killer became a generic product category name rather than a brand name and drug criticism and regulation limited its formulation and ability to advertise using cure-all claims.